2015
DOI: 10.1002/pola.27768
|View full text |Cite
|
Sign up to set email alerts
|

PEGDA‐based luminescent polymers prepared by frontal polymerization

Abstract: Frontal polymerization (FP) of poly(ethylene glycol) diacrylate (PEGDA) was carried out using benzoyl peroxide (BPO) as radical initiator. In addition, a pyrene containing monomer, 1-pyrenebutyl acrylate (PyBuAc), was incorporated as a fluorescent probe in order to obtain luminescent materials with different chromophore contents. The resulting polymers were characterized by FT-IR spectroscopy in the solid state and their thermal properties were determined by thermogravimetric analysis (TGA) and differential sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Since the pioneering work of Chechilo in 1972 on the synthesis of poly(methyl methacrylate), 1 FP has been studied deeply and applied widely in many fields, such as functional gradient materials, 2 composite materials 3 and luminescent materials. 4 FP has also been proposed as a new method for developing functional hydrogels because of its easy and convenient protocol. Washington and Steinbock 5 first demonstrated that FP enables the preparation of homogeneous poly(N-isopropylacrylamide) (PNIPAm) hydrogels without compromising their temperature-dependent property.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the pioneering work of Chechilo in 1972 on the synthesis of poly(methyl methacrylate), 1 FP has been studied deeply and applied widely in many fields, such as functional gradient materials, 2 composite materials 3 and luminescent materials. 4 FP has also been proposed as a new method for developing functional hydrogels because of its easy and convenient protocol. Washington and Steinbock 5 first demonstrated that FP enables the preparation of homogeneous poly(N-isopropylacrylamide) (PNIPAm) hydrogels without compromising their temperature-dependent property.…”
Section: Introductionmentioning
confidence: 99%
“…Frontal polymerization (FP) is a method of spontaneous directional propulsion reaction that converts monomers into polymers in a localized reaction zone. Since the pioneering work of Chechilo in 1972 on the synthesis of poly(methyl methacrylate), FP has been studied deeply and applied widely in many fields, such as functional gradient materials, composite materials and luminescent materials …”
Section: Introductionmentioning
confidence: 99%
“…These results assume that the incorporation of pyrene and perylene copolymers did not significantly change the glass transition temperature of the prepared hydrogels and this may be due to the low content of the pyrene and perylene copolymers. The hydrogel that incorporated polyethylene glycol (AH21) exhibited two semicrystalline peaks 78 between 30 °C and 45 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Adjusting the photophysical or electrical properties of easily synthesizable polymers represents an attractive alternative method to generate organic components for devices. A substantial volume of work has focused on the synthesis of frontally derived polymers embedded with colloidal quantum dots (CQDs), 74,257,[265][266][267]295,350 carbon dots (CDots), 206,257 carbon nanotubes, 158 and other inorganic nanoparticles. 157,351 The light absorption behavior of these nanometer-sized inorganic clusters are easily modified; 352 as a result of quantum confinement, the size of the material directly impacts the λmax as observed in an example where the size of PbS nanoparticles influenced the observed color.…”
Section: Photoluminescent and Thermochromic Compositesmentioning
confidence: 99%